A human breast atlas integrating single-cell proteomics and transcriptomics - Gray, G. Kenneth; Li, Carman Man-Chung; Rosenbluth, Jennifer M.; Selfors, Laura M.; Girnius, Nomeda; Lin, Jia-Ren; Schackmann, Ron C.J.; Goh, Walter L.; Moore, Kaitlin; Shapiro, Hana K.; Mei, Shaolin; D’Andrea, Kurt; et al. (Developmental cell, 2022)
The breast is a dynamic organ whose response to physiological and pathophysiological conditions alters its disease susceptibility, yet the specific effects of these clinical variables on cell state remain poorly annotated. We present a unified, high-resolution breast atlas by integrating single-cell RNA-seq, mass cytometry, and cyclic immunofluorescence, encompassing a myriad of states. We define cell subtypes within the alveolar, hormone-sensing, and basal epithelial lineages, delineating associations of several subtypes with cancer risk factors, including age, parity, and BRCA2 germline mutation. Of particular interest is a subset of alveolar cells termed basal-luminal (BL) cells, which exhibit poor transcriptional lineage fidelity, accumulate with age, and carry a gene signature associated with basal-like breast cancer. We further utilize a medium-depletion approach to identify molecular factors regulating cell-subtype proportion in organoids. Together, these data are a rich resource to elucidate diverse mammary cell states. [Display omitted] •Multimodal single-cell analyses identify breast epithelial and stromal subtypes•Spatially distinct epithelial subsets are linked with age, parity, and BRCA2 status•Alveolar cells with poor transcriptional lineage fidelity accumulate with age•Subtypes of the three major epithelial lineages are maintained in organoid cultures Gray, Li, Rosenbluth, Selfors et al. generate a multi-dimensional atlas of breast tissues and organoids. Distinct epithelial subtypes are found to be associated with age, parity, and BRCA2 mutation. An alveolar subset termed basal-luminal cells displays poor transcriptional lineage fidelity and gene expression signatures associated with aggressive basal-like breast cancers.